INCOME COMPONENTS AND POVERTYAMONG OLDER MEN AND WOMEN IN MALAYSIA - Ismail, Norisma Aiza; Masud, Jariah; Zainalaludin, Zumilah (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
The study aims to identify the income components and the incidence of poverty among older men and women in Malaysia. A national data on Household Income Survey (HIS) collected in year 2009-2010 was used in this study. Data from subsample of 16,325 out of 43,026 older persons was used in the analysis. The respondents comprised of 47.9% male and 52.1% female with an equal proportion living in urban and rural areas. The total net income was used to determine poverty status among respondents who reported receiving income. Income Per Capita was used to determine the poverty status. Resultsindicated thata there were 42.3% older persons did not receive any income and can be assumed to be dependent on others to support their living. Only 57.7% of the elderly received income from the four main sources namely paid employment, other earned income, property income and total current transfer income. Majority of the elderly received income from other earned income as well as total current transfer income. Overall, a higher proportion of men received income from all sources except transfer income. A small percentage of the elderly received income from paid employment. This reflects that majorityof the elderly are no longer employed. In addition, a large proportion of the elderly rely on other earned and transfer income in old age. Older women are more vulnerable to poverty in old age. Even though a higher percentage of olderpersons, especially women, received income from total current transfer, however this income component is still insufficient to address poverty among older persons. Thus, as part of productive ageing strategies, focus should be given on providing more job opportunities to enable older persons to increase their income.